USES OF VIRTUAL REALITY IN PHYSICAL REHABILITATION: A SYSTEMATIC REVIEW - DÁVILA-MORÁN, ROBERTO CARLOS (2024)
VIRTUAL REALITY (VR) HAS EMERGED AS AN INNOVATIVE TOOL IN THE FIELD OF PHYSICAL REHABILITATION (PR), OFFERING AN IMMERSIVE APPROACH TO IMPROVE MOTOR FUNCTION AND QUALITY OF LIFE IN PATIENTS. HOWEVER, THE EFFECTIVENESS OF VR COMPARED TO OTHER REHABILITATION METHODS REMAINS UNDER STUDY. THE PRESENT STUDY AIMS TO ANALYZE THE USES OF VR IN PR THROUGH A SYSTEMATIC REVIEW OF THE AVAILABLE LITERATURE, ASSESSING ITS IMPACT ON PHYSICAL FUNCTION AND QUALITY OF LIFE IN PATIENTS. A SYSTEMATIC REVIEW WAS CONDUCTED FOLLOWING PRISMA GUIDELINES. 21 STUDIES PUBLISHED BETWEEN 2014 AND 2024 WERE SELECTED, OBTAINED FROM DATABASES SUCH AS SCOPUS, SCIENCEDIRECT, AND EBSCO. THE STUDIES INCLUDED DIVERSE POPULATIONS REQUIRING PR USING IMMERSIVE AND NON-IMMERSIVE VR TECHNOLOGIES. THE STUDIES SHOWED THAT IMMERSIVE VR PROVIDED GREATER IMPROVEMENTS IN BALANCE AND GAIT, ESPECIALLY IN PATIENTS WITH PARKINSON'S, COMPARED TO NON-IMMERSIVE VR. INTERVENTIONS WITH IMMERSIVE VR ALSO RESULTED IN GREATER TREATMENT ADHERENCE DUE TO THEIR INTERACTIVE NATURE. HOWEVER, STUDIES PRESENT HETEROGENEITY IN TERMS OF TECHNOLOGIES AND POPULATIONS STUDIED, WHICH AFFECTS THE GENERALIZABILITY OF THE RESULTS. VR HAS GREAT POTENTIAL TO IMPROVE RF, BUT ITS EFFECTIVENESS DEPENDS ON FACTORS SUCH AS THE TECHNOLOGY USED AND THE CONDITION OF THE PATIENTS. LARGER-SCALE STUDIES WITH CONTROLLED EXPERIMENTAL DESIGNS ARE RECOMMENDED TO VALIDATE THESE FINDINGS AND EXPLORE THE IMPACT OF VR IN HOME REHABILITATION CONTEXTS. © 2024 FEDERACION ESPANOLA DE DOCENTES DE EDUCACION FISICA. ALL RIGHTS RESERVED.